Praktik Audit Sistem Informasi: Sebuah Langkah Menuju Kematangan Tata Kelola Sistem Informasi - Hapsari, Aprina Nugrahesthy Sulistya; Yofinda, Samuel Putra; Theotama, Gracella (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2022)
Society 5.0 necessitate every company to be able to optimize information technology resources that continue to grow in order to have competitiveness, especially the pandemic. This also needs to be supported by optimal IS / IT governance owned by the company, so as to minimize errors and other obstacles. Therefore, it is necessary to have an information system audit to assess capabilities and provide an evaluation so that the company is able to create better risk management. This research aims to assess the level of capability and evaluation of the information system implemented by Adira Finance, especially branch companies in the Salatiga City, using the COBIT 5 framework. Data were obtained by conducting interviews and observations to employees related to IT, and analyzed by qualitative descriptive method. The result of this study shows that the average capability level in each domain is level 1 (performed process), so it can be said that the system is able to operate properly